PREECLAMPSIA CARE (A WEB-BASED INFORMASTION SYSTEM) EFFECTIVE FOR DETECTING THE RISK OF PREECLAMPSIA IN PREGNANT WOMEN - Fajaria Nur Aini; Fitria Zuhriyatun; Diki Retno Yuliani; Wanodya Hapsari (Universitas Karya Husada Semarang, 2024)
One of the leading causes of maternal and newborn fatalities worldwide is preeclampsia. Only healthcare professionals can now detect the risk of preeclampsia, and they still do so manually. Pregnant women can't know if they have preeclampsia risk factors or not. Preeclampsia risk detection is significant because it can determine a pregnant woman's preeclampsia risk, allowing for early diagnosis and prevention. A web-based information system can be used to identify pregnant women who are at risk of preeclampsia. Women who are expecting can utilize laptops or smartphones linked to the internet. Numerous research studies have demonstrated that information technology solutions can enhance health services regarding data transmission, health outcomes, prescription adherence, and patient monitoring compliance. This descriptive study explained its usefulness; live sampling was used as the sampling method, and 33 pregnant women served as the study's subjects. Web-based information systems and questionnaires are used to collect data. Pregnant women's ability to independently recognize preeclampsia risk can be enhanced by employing a web-based information system to identify different levels of preeclampsia risk. Of these, 51.5% have no risk of preeclampsia, 18.2% have a moderate risk, and 24.24% have a high risk. The effectiveness rate used in the Technology Acceptance Model (TAM) questionnaire is 92%.